Physico-chemical Qualities of Solar Dried Fruits of Karonda (Carisa carandus L.) as Affected by Blanching and Potassium Metabisulphite - Lal, G (Annals of Arid Zone, 2016)
The effect of b!’n<hing ,nd polaium metabisnlphHe on Physi’<Xh=i ! q=liti’" of solar dried fruits of karonda (Carisa carandus L.) for obtaining good quality dned produce was studied. Karonda fruits were subjected to different processing treatments vizj, blanching, without blanching and potassium metabisulphite (0.5% and 1.0%) and dried i1 solar drier and their quality assessed. The fruits blanched for 5 minutes and sulphitation fith + 0.5% KMS for 15 minutes exhibited maximum dry matter recovery (16.76%), reconstttution ratio (3.93), acidity (0.515%) and ascorbic acid (40.75 m, g/lOO-g). The consumer acc!ptability of the fruits under this treatment was highest with maximum organoleptic sco1e (8.04 Â